2015
DOI: 10.1002/2015jd023665
|View full text |Cite
|
Sign up to set email alerts
|

Atmospheric responses to the redistribution of anthropogenic aerosols

Abstract: The geographical shift of global anthropogenic aerosols from the developed countries to the Asian continent since the 1980s could potentially perturb the regional and global climate due to aerosol-cloud-radiation interactions. We use an atmospheric general circulation model with different aerosol scenarios to investigate the radiative and microphysical effects of anthropogenic aerosols from different regions on the radiation budget, precipitation, and large-scale circulations. An experiment contrasting anthrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
61
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 98 publications
(66 citation statements)
references
References 48 publications
5
61
0
Order By: Relevance
“…However, the aerosol perturbations at cloud-scale affect the regional and global circulation, and these regional-through global scale changes feed back as meteorological influences on cloud processes [112,133,150,151]. This means that constraining ERF aci requires understanding the microscale, the cloud process scale, and the global scale, as well as the interactions between scales.…”
Section: Why Are Erf Aci Estimates So Challenging?mentioning
confidence: 99%
“…However, the aerosol perturbations at cloud-scale affect the regional and global circulation, and these regional-through global scale changes feed back as meteorological influences on cloud processes [112,133,150,151]. This means that constraining ERF aci requires understanding the microscale, the cloud process scale, and the global scale, as well as the interactions between scales.…”
Section: Why Are Erf Aci Estimates So Challenging?mentioning
confidence: 99%
“…Besides the local aerosol sources, the atmospheric transport of aerosol pollutants from the Asian continent (e.g., Jiang et al, 2007;Wang et al, 2015;Hu et al, 2016) is also a significant contributor to aerosol loading throughout the Pacific basin. Asian aerosols can reach relatively high concentrations above the marine boundary layer in the western US, representing as much as 85 % of the total atmospheric burden of PM at some sites (VanCuren, 2003).…”
mentioning
confidence: 99%
“…A recent study by Y. Wang et al . [] indicated that the spatial redistribution of aerosols might have significant implications for large‐scale circulation. In addition, the seasonal variation of vertical cloud structures is different which may induce different aerosol‐cloud microphysics interactions [ Wang et al ., ].…”
Section: Introductionmentioning
confidence: 85%
“…Many modeling and observational studies have been conducted to investigate aerosol‐cloud‐radiation‐precipitation interactions [ Ackerman et al ., ; Guo et al ., ; Rosenfeld , ; Tao et al ., ; Twomey , ; H. Wang et al ., ; Y. Wang et al ., ]. Most aerosol‐cloud interaction studies that involve warm clouds find consistent responses in cloud properties: more aerosols result in more, but smaller, cloud droplets and thus enhanced cloud albedo if the total water keeps constant.…”
Section: Introductionmentioning
confidence: 99%